Communication error management in law enforcement interactions: a receiver’s perspective - Oostinga, Miriam S. D. (Psychology, crime & law, 2018)
Two experiments explore the effect of law enforcement officers’ communication errors and their response strategies on a suspect’s trust in the officer; established rapport and hostility; and, the amount and quality of information shared. Students were questioned online by an exam board member about exam fraud (Nstudy1 = 188) or by a police negotiator after they had stolen money and barricaded themselves (Nstudy2 = 184). Unknown to participants, the online utterances of the law enforcement officer were pre-programmed to randomly assign them to a condition in a 2(Error: factual, judgment) × 3(Response: contradict, apologize, accept) factorial design, or to control where no error was made. Our findings show that making (judgment) errors seem more detrimental for affective trust and rapport in a suspect interview, while no such effects appeared in a crisis negotiation. Notably, we found a positive effect of errors, as more information was being shared. The ultimate effect of the error was dependent on the response: accept was effective in re-establishing rapport and decreasing hostility, while contradict threatens it. Accept seems more effective for the willingness to provide information in a suspect interview, while apologize seems more effective for affective trust and rapport in a crisis negotiation.